2017
DOI: 10.1016/j.jvs.2016.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, nonrandomized study to evaluate endovascular repair of pararenal and thoracoabdominal aortic aneurysms using fenestrated-branched endografts based on supraceliac sealing zones

Abstract: Endovascular repair of pararenal aortic aneurysms and TAAAs, using manufactured F-BEVAR with supraceliac sealing zones, is safe and efficacious. Long-term follow-up is needed to assess the impact of four-vessel designs on device-related complications and progression of aortic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(138 citation statements)
references
References 30 publications
7
128
1
2
Order By: Relevance
“…Type 3 endoleaks, described by Mastracci et al as endoleaks from bridging stent disconnection to the fenestration or disconnection between two bridging stents, 5 are reported to be the major cause of re-intervention following complex endovascular repair. 22 In practice with this new generation stent, flaring is very efficient, and the present authors have not observed any type 3 endoleaks. The aortic portion of the stent, which is very well visualised (cobaltchromium alloy offers an opacity that allows accurate positioning during deployment) during the procedure, conformed very well to the 10 mm diameter flaring balloon, and provided a durable seal at the connexion with the nitinol reinforced fenestrations.…”
Section: Discussionsupporting
confidence: 53%
“…Type 3 endoleaks, described by Mastracci et al as endoleaks from bridging stent disconnection to the fenestration or disconnection between two bridging stents, 5 are reported to be the major cause of re-intervention following complex endovascular repair. 22 In practice with this new generation stent, flaring is very efficient, and the present authors have not observed any type 3 endoleaks. The aortic portion of the stent, which is very well visualised (cobaltchromium alloy offers an opacity that allows accurate positioning during deployment) during the procedure, conformed very well to the 10 mm diameter flaring balloon, and provided a durable seal at the connexion with the nitinol reinforced fenestrations.…”
Section: Discussionsupporting
confidence: 53%
“…Because this patient had a single iliac access available and we were concerned about successful renal cannulation through fenestrations and previously placed bare-metal stent in an angulated visceral aorta, we decided to treat him using a modified closed web Valiant device with one fenestration for (14) Peripheral artery disease 5 (7) 7 (25) .03 12 (12) History of aortic surgery 9 (13) 7 (25) . 22 16 (16) ASA class the superior mesenteric artery that was cannulated from an axillary access and two chimney grafts for renal arteries.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the treatment of CAAAs by CMSGs, our 4% inhospital mortality rate is in line with previous reports from high-volume centers. [21][22][23][24][25] Compared with our initial results, 26 short-term outcomes improved significantly with larger experience. Of the three deaths in the CMSG group, two occurred in our early experience in patients with shaggy aortas, which are currently considered strict contraindications to fenestrated stent grafts.…”
Section: Iliofemoral Bypass 2 (3) 1 (4) 3 (3)mentioning
confidence: 89%
See 1 more Smart Citation
“…Fenestrated and branched endografts have broadened the indications of endovascular aortic repair to patients with complex aneurysms involving the renal and mesenteric arteries 4, 5. In most centers with larger experience, fenestrated stent grafts have evolved from two fenestrations to three or four fenestrations based on supraceliac sealing zones.…”
Section: Discussionmentioning
confidence: 99%